Financing sustainability: Applying the BIOFIN framework to government investments in conserving native and indigenous livestock breeds in central India - Bakul Lad; Faiyaz A. Khudsar; Ajay Sharma; Randeep Singh (PLoS ONE, 2025)
Biodiversity conservation is a key responsibility for signatories of the Convention on Biodiversity. India is legally committed to the Aichi Biodiversity Targets (ABTs) and the United Nations’ sustainable development goals (SDGs), with a focus on protecting its livestock diversity and genetic resources. Livestock diversity is crucial for maintaining ecosystem functionality and supporting the livelihoods of indigenous communities by contributing to the rural economy. However, urbanization, rapid land use changes, agricultural mechanization, loss of pastoral lands, and emerging diseases have significantly reduced indigenous livestock diversity. The growing demand for high-yield livestock breeds further threatens native and indigenous varieties. This study examines the financial mechanisms employed by the public sector Animal Husbandry Department in Madhya Pradesh, India, using the Biodiversity Finance Initiative (BIOFIN) framework. It assesses the availability of funding across five BIOFIN categories—conservation, sustainable use, education and awareness, policy, and access and benefit sharing—to meet state biodiversity targets aligned with the Aichi Targets. A total of 43 schemes were identified and mapped to these categories. From 2016 to 2022, approximately INR 5,159.88 crore (~US $727.4 million) was invested in livestock conservation and sustainable production in the state. The BIOFIN methodology has facilitated robust financial planning for the livestock sector. The sector is meeting the financial needs assessed in the Madhya Pradesh Biodiversity Strategy and Action Plan, 2018−30, through systematic investments for the conservation and sustainability of livestock biodiversity with an effective awareness extension program. While progress has been made, the emphasis on increasing native livestock production continues to pose challenges to biodiversity conservation.